2014
DOI: 10.1016/j.schres.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Stress exposure and sensitivity in the clinical high-risk syndrome: Initial findings from the North American Prodrome Longitudinal Study (NAPLS)

Abstract: There is inconsistent evidence for increased stress exposure among individuals at clinical high risk (CHR) for psychosis. Yet, similar to patients with a diagnosed psychotic illness, the preponderance of evidence suggests that CHR individuals tend to experience stressful life events (LE) and daily hassles (DH) as more subjectively stressful than healthy individuals. The present study utilizes data from the North American Prodrome Longitudinal Study Phase 2 (NAPLS-2) to test the hypotheses that 1) CHR individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…As expected, and consistent with previous studies (e.g., 9, 49), the association of both types of stressors with PEs was also greater in the early‐psychosis group compared to the non‐clinical group (even if the latter was oversampled for elevated scores on schizotypy to include a wide range of variability in terms of psychosis liability). Results thus seem to indicate that, although comparable mechanisms, such as stress sensitivity, operate across different levels of psychotic liability, and expression, there is also a differential impact of stressors in both groups reflecting individual differences in risk and resilience factors, some of which may pave the way toward psychotic outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, and consistent with previous studies (e.g., 9, 49), the association of both types of stressors with PEs was also greater in the early‐psychosis group compared to the non‐clinical group (even if the latter was oversampled for elevated scores on schizotypy to include a wide range of variability in terms of psychosis liability). Results thus seem to indicate that, although comparable mechanisms, such as stress sensitivity, operate across different levels of psychotic liability, and expression, there is also a differential impact of stressors in both groups reflecting individual differences in risk and resilience factors, some of which may pave the way toward psychotic outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…This has been supported by numerous subsequent studies (Holtzman et al, 2013). Similarly, CHR patients who later converted to psychosis reported a greater number of life events, and perceived these events as more stressful, compared to healthy controls and CHR subjects whose symptoms remitted (Trotman et al, 2014). Perceived stress levels in CHR patients are generally high (Moskow et al, 2016), and in some studies they even exceed ratings in FEP patients (Pruessner et al, 2011, Palmier-Claus et al, 2012.…”
Section: Stress Exposure Perceived Stress and Early Life Adversitymentioning
confidence: 72%
“…Both animal (Liu et al, 1997, Anisman et al, 1998 and human (Devylder et al, 2013, Trotman et al, 2014 studies have shown that previous exposure to stressful events can lead to stress-sensitization and dysregulation of the HPA response when confronted with subsequent stressors, both of which are believed to be critical contributors to the development of psychosis. Trauma victims not only responded with more subjective distress to stressful experiences later in life (Veling et al, 2016), the experience of early life adversity also predicted attenuated cortisol responses to a public speaking task in a dose-dependent fashion (Lovallo et al, 2012).…”
Section: Stress Exposure Perceived Stress and Early Life Adversitymentioning
confidence: 99%
“…For example, CHR individuals report more stress than healthy controls (HCs) (Cullen et al, 2014; Pruessner et al, 2011). In a report based on the first half of the North American Prodrome Study (NAPLS-2) cohort, aged 13 to 30 years, CHR subjects reported more daily stress than HCs, and the CHR subjects who subsequently converted to psychosis reported greater stress than remitted CHR subjects, with those who remained prodromal falling in between (Trotman et al, 2014). Also, of interest to note, there was a trend for a more pronounced relation between stress and age for the CHR group.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are now enough subjects in the 13 to 19 year age-range to examine TS. Based on the evidence that both stress indices and prodromal/psychotic symptoms increase through the adolescent years, and that age-related increases in stress may be greater for CHR subjects (Trotman et al, 2014), it is hypothesized that CHR youth will show a more pronounced relation of age and Tanner pubertal stage with self-reported daily stress and basal cortisol.…”
Section: Introductionmentioning
confidence: 99%